ISLAMIC VALUES IN MATHEMATICS LEARNING THROUGH THE REALISTIC MATHEMATICS EDUCATION (RME) MODEL - Ukhti Raudhatul Jannah; Agus Subaidi; Towafi Towafi (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
Mathematics is one of the subjects that are less attractive to students who attend Islamic boarding schools. They assume that mathematics has nothing to do with Islamic values. Whereas mathematics material has a relationship with Islamic values such as the material for arithmetic sequences and series. In this case, a teacher needs to use the right learning model to deliver the subject matter, for example with the Realistic Mathematics Education (RME) model. RME is a model of mathematics learning that can connect mathematics learning objects with real life so that students can easily understand mathematics. This study aims to describe the effect of internalizing Islamic values in mathematics learning through the Realistic Mathematics Education (RME) model in arithmetic sequences and series subjects which were carried out for two meetings. The research method used is descriptive qualitative method with the research subjects are 29 students of class XI IPA MA Matsaratul Huda. Data collection techniques used teacher and student activity observation sheets, student response questionnaire sheets, documentation, and test sheets. The results of the observation data analysis of teacher and student activities can be categorized as "very good" and students also respond "positively" to learning. From the results of student learning tests can be said to be "complete" classically with the results of 89.65% 85%. Based on the results of this study, it can be said that the internalization of Islamic values in mathematics learning through Realistic Mathematics Education (RME) affects student learning activities and outcomes and helps students understand the material and can provide new knowledge about the relationship between mathematics and Islamic values. This research can be used as an alternative in providing better learning.